2005
DOI: 10.1007/s10107-005-0652-x
|View full text |Cite
|
Sign up to set email alerts
|

Projection results for vehicle routing

Abstract: Abstract.A variety of integer programming formulations have been proposed for Vehicle Routing Problems (VRPs), including the so-called two-and three-index formulations, the set partitioning formulation, and various formulations based on extra variables representing the flow of one or more commodities. Until now, there has not been a systematic study of how these formulations relate to each other. An exception is a paper of Luis Gouveia, which shows that a one-commodity flow formulation of Gavish and Graves yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 31 publications
2
86
0
Order By: Relevance
“…It is easy to show that all of the inequalities which are assignable for the traveling salesman game are also assignable for the vehicle routing game. Moreover, further assignable inequalities were presented in [25]. (They were called decomposable inequalities in that paper.)…”
Section: The Vehicle Routing Gamementioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to show that all of the inequalities which are assignable for the traveling salesman game are also assignable for the vehicle routing game. Moreover, further assignable inequalities were presented in [25]. (They were called decomposable inequalities in that paper.)…”
Section: The Vehicle Routing Gamementioning
confidence: 99%
“…Other assignable inequalities discussed in [25] include the Knapsack Large Multistar (KLM) inequalities [24], which are a generalization of the GLM inequalities, and the so-called hypotour-like inequalities. While the complexity of the separation problem for the KLM inequalities is unknown, a generalization of the hypotour-like inequalities can be separated efficiently [25].…”
Section: Corollarymentioning
confidence: 99%
“…Dell'Amico et al [3] basically extended the one-commodity flow formulation proposed by Gavish and Graves [7] for the CVRP by adding constraints (6) and (9), and the term P ij in (7). Gouveia [8] showed that it is possible to obtain stronger inequalities for D ij by using the tighter bounds (11) instead of (8) in the Gavish and Graves formulation.…”
Section: One-commodity Flow Formulationmentioning
confidence: 99%
“…Gouveia [8] showed that it is possible to obtain stronger inequalities for D ij by using the tighter bounds (11) instead of (8) in the Gavish and Graves formulation. Accordingly, we can apply the same idea to develop stronger inequalities for P ij by replacing (9) with (12) and for D ij + P ij by replacing (7) with (13).…”
Section: One-commodity Flow Formulationmentioning
confidence: 99%
See 1 more Smart Citation